Principle of khiyar al-ru’yah and Its application according to Islamic law as proposed by Muslim jurists. - Awang Hamat, Mohd Afandi; Abd Halim, Syakirah (International Islamic University Malaysia (IIUM), 2014)
This paper examines the right of Consumers according to Islamic Law in their business transaction in the light of Khiyar al-Rukyah. Islam as the religion revealed by Allah SWT demands mankind to work hard in order to gain livelihood in this worldly life. However, they must make sure that properties obtained by them must be legal and halal. Thus, Allah SWT did not allow any Muslim to seek properties through illegal (haram ) means. Khiyar al-ru’yah or option at sight or option on inspection is generally defined in Islamic law as a right of purchaser either to confirm the sale and purchased agreement or to reject it after having seen the subject-matter of contract. This implies that if a person purchases from the vendor an article without having seen it during the time of contract, the sale of such article is valid, and the purchaser after seeing it has the option of accepting or rejecting that article. This paper shall highlight the definition of khiyar al-ru’yah, rationale behind the legality of khiyar al-ru’yah, evidence on the legality of khiyar al-ru’yah, view of Muslim jurists about the application of khiyar al-ru’yah, the essence of viewing in respect to khiyar al-ru’yah, condition of valid option in respect to khiyar al-ru’yah and its Optional period in khiyar al-ru’yah. Finally this paper will provide conclusion for the various issues discussed in this topic. It is hoped that this paper will insha’Allah provide some benefits for the Muslim in order to understand their rights in regard to khiyar al-ru’yah.